Dynamic Effects of Economic Liberalization, Privatization, and Globalization on the Export Performance of Ethiopian Privatized Manufacturing Firms - Mohammed Ahmed Endris; Abebe Ejigu Alemu; Abiot Tsegaye Kibret (Administrative Sciences)
This study investigates the dynamic effect of economic liberalization, privatization, and globalization on the export performance of Ethiopian manufacturing firms. We use structural equation modeling (SEM) to examine the direct and indirect influences between these macroeconomic reforms and export performance, which are mediated by firms’ competitive priorities in the global market, using cross-sectional data from 114 manufacturing privatized manufacturing firms by using key informant techniques. The study looks into how firms’ export competitiveness and export performance are affected by economic liberalization, privatization, and global market integration since 1991 national economic reform. This model identified liberalization, privatization, and globalization as independent variables that mediated export performance under competitive priority. The findings of the proposed framework showed that all of the predictive variables (LPG) were significant at p < 0.05, indicating that liberalization, privatization, and economic globalization influence export performance across all competitive priorities. The result further revealed that by expanding access to international markets and promoting competitive efficiency, economic globalization/integration, privatization incentives, and economic liberalization changes all significantly improve export performance. The results also infer that LPG provides an intervening role in boosting export performance under firms’ competitive priorities (cost, flexibility, and quality). However, resolving issues, including inefficient regulations and inconsistent incentives, is important to realize these advantages. To optimize the advantages of these dynamics, policymakers must concentrate on establishing a business environment that encourages firms to partake in export, innovation, and competition. The study contributes to the literature by offering sector-specific insights for policymakers aiming to optimize privatization strategies and trade reforms to boost Ethiopia’s manufacturing exports. The results underscore the need for targeted policy interventions to mitigate short-term disruptions while maximizing long-term export gains in a liberalized economy.